Seismic fragility curves for legged wine storage tanks with a novel isolation device. (2017) - Colombo, J.I.; Almazán, J.L.
Abstract: Seismic protection of wine storage tanks has become a very important issue due to the boom of the winery industry in some seismic countries such as, the U.S, Italy, New Zealand, Chile and Argentina. Wine storage tanks are classified in two major groups: continuously supported tanks and legged tanks. Previous research has developed fragility curves for continuously supported tanks, with and without seismic protection devices, in order to establish the seismic reliability of this kind of tanks. However, fragility curves of legged wine tanks have not been reported. Therefore, in this study, the fragility curves of a typical stainless steel legged wine storage tank (one of 3, 000 litres capacity), used for fermentation and wine storage, are assessed by means of numerical simulation. The fragility curves were developed by the results obtained from a mathematical model capable to perform the nonlinear time history analysis of the tank subjected to several artificial ground motions. The artificial ground motions are based on ground motion prediction from earthquakes recorded in Chile. Finally, the seismic fragility for a typical legged wine storage located in Chile was presented. Furthermore, the seismic fragility of a same damage state for a typical legged wine storage tank with and without a novel isolation device were compared.